Recommendations for the programme of clinical trials of medicinal products for the treatment of influenza - A. I. Gubenko; G. V. Shukshina; A. I. Muravieva; N. E. Uvarova (Регуляторные исследования и экспертиза лекарственных средств)
Scientific relevance. The development of new medicinal products to treat influenza is motivated by the limitations of existing treatment options, the emergence of drug resistance, and the health consequences of influenza epidemics associated with the highly contagious nature of the virus. Proper planning and implementation of clinical programmes providing reliable data on the efficacy and safety of medicinal products under development requires adherence to recommendations of the regulatory authorities. At the moment, the Russian Federation, the Eurasian Economic Union, and the European Union lack documented recommendations on conducting clinical trials of anti-influenza medicines. There is a need in national guidelines that will reflect the procedure for conducting clinical trials and establish the required amount of data to be submitted with marketing applications for new anti-influenza products.Aim. The study was aimed to analyse possible regulatory approaches to planning clinical development programmes for anti-influenza medicinal products.Discussion. The article pays particular attention to phase III studies, as the main studies confirming efficacy and safety. The authors described a clinical development strategy and the requirements for the volume and quality of efficacy and safety data. This article is based on the current Russian recommendations for the design and development of medicinal products and guidelines on their evaluation, as well as the recommendations by the U.S. Food and Drug Administration (FDA).Conclusions. The analysis results demonstrate the necessity for elaborating Russian recommendations for clinical studies of medicinal products for the treatment of influenza that will take into account the national legislation and clinical development practices. Such recommendations will streamline the implementation of new effective anti-influenza medicinal products.